Agricultural Soils of Florida - Rao Mylavarapu; Willie Harris; George Hochmuth (EDIS)
This 7-page fact sheet describes the various soil Orders in Florida, how they were developed, their characteristics, coverage in the state, and uses. This information is important for educating land owners, decision-makers, and educators about soils in Florida, leading to better soil management for agricultural and environmental sustainability. Written by Rao Mylavarapu, Willie Harris, and George Hochmuth, and published by the Soil and Water Sciences Department, October 2016.